Examining Key Determinants of Customer Satisfaction in the Post-Pandemic Cinema Experience - Ainul Mohsein Binti Abdul Mohsin; A. J. Ali; Daisy Mui Hung Kee; Muhammad Danish Haikal Bin Mohamad Nassa; Muhammad Afiq Adid Bin Sharuddin; Muhammad Aiman Bin Mohd Hatta; Muhammad Asyqar Widad Bin Mohd Azrol Nizam; Muhammad Danish Akmal Bin Kamarudin (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
Customer satisfaction has become an important performance indicator for entertainment service providers such as cinemas, particularly in a competitive industry driven by experience and content quality. This study aims to analyze the factors influencing customer satisfaction toward Golden Screen Cinema (GSC) in Malaysia by examining five key determinants: ambience, service quality, accessibility, pricing, and movie genre. Using multiple regression analysis on data from 104 respondents, the findings reveal that ambience (? = 0.296, p 0.01) and movie genre (? = 0.313, p 0.001) have significant positive effects on customer satisfaction. In contrast, service quality (? = 0.172), accessibility (? = 0.045), and pricing (? = 0.138) do not significantly influence satisfaction. The model explains 68.1% of the variance in customer satisfaction (R² = 0.681), indicating strong explanatory power. The results suggest that the cinema experience and film selection are the main drivers of customer satisfaction, emphasizing the importance of enhancing environmental quality and curating appealing movie offerings to maintain customer satisfaction in the entertainment industry.